Complement Receptor-Mediated Phagocytosis Induces Proinflammatory Cytokine Production in Murine Macrophages - Acharya, Durga; Li, Xiao Rui (Lisa); Heineman, Rebecca Emily-Sue; Harrison, Rene E. (Frontiers in Immunology, 2020)
Macrophages are professional phagocytes that are uniquely situated between the innate and adaptive arms of immunity with a high capacity for phagocytosis and proinflammatory cytokine production as well as antigen presentation. Phagocytosis is a critical process to eliminate microbes, apoptotic cells and other foreign particles and is accelerated by host-generated opsonins, such as antibodies and complement. Early phagocytosis studies established the paradigm that FcγR-mediated phagocytosis was more proinflammatory than Complement Receptor (CR)-mediated uptake in macrophages. Using qPCR, cytokine antibody arrays and ELISA, we revisited this research question in primary macrophages. Using qPCR we determined that CR-mediated phagocytosis increases levels of TNF-α, IL-1β, IL-6, and MMP-9, compared to FcγR-mediated phagocytosis and control unstimulated cells. We confirmed these findings at the protein level using cytokine antibody arrays and ELISAs. We next investigated the mechanism behind upregulated cytokine production during CR-mediated phagocytosis. IκBα protein levels were reduced after phagocytosis of both IgG- and C3bi-sRBCs indicating proteolytic degradation and implicating NF-κB activation. Inhibition of NF-κB activation impacted IL-6 production during phagocytosis in macrophages. Due to the roles of calpain in IκBα and integrin degradation, we hypothesized that CR-mediated phagocytosis may utilize calpain for proinflammatory mediator enhancement. Using qPCR and cytokine antibody array analysis, we saw significant reduction of cytokine expression during CR-mediated phagocytosis following the addition of the calpain inhibitor, PD150606, compared to untreated cells. These results suggest that the upregulation of proinflammatory mediators during CR-mediated phagocytosis is potentially dependent upon calpain-mediated activation of NF-κB.